Letter : Mr J. C. Navas - Hallsworth, Joseph
001-0092-001 Telephone & Telegrams : Rusholme 2804. (five lines) 'Oakley' 122, Wilmslow Road, MANCHESTER, 14 JH/RC 30th November 1944 Mr. H.B. Kemmis, Secretary, Trades Union Congress, Colonial Advisory Committee, Transport House, Smith Square. S.W.I. Dear Mr. Kemmis, Mr. J.C. Navas I thank you for your letter (and enclosure) of the 27th November (HBK/DT/222), the contents of which have been duly noted. Yours sincerely, J. Hallsworth. 292/946/1/92